Perovskite precursor solution additive, perovskite solar cell and preparation method

By using a mixed solution of hydrochloric acid or organic amine hydrochloride as an additive in perovskite solar cells, the crystallization of perovskite is controlled, which solves the defect problem of perovskite solar cells when they are prepared in air and improves the stability and efficiency of the device.

CN120957578APending Publication Date: 2025-11-14ZHEJIANG UNIV +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510886883.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-30
Publication Date
2025-11-14

AI Technical Summary

Technical Problem

When perovskite solar cells are fabricated in air, defects easily form at grain boundaries and interfaces, leading to ion migration and material sensitivity to water and oxygen, which affects stability and efficiency.

Method used

A mixed solution of DMF and deionized water in hydrochloric acid or organic amine hydrochloride is used as an additive to regulate perovskite crystallization, prepare a perovskite light-absorbing layer, reduce defects, and improve device performance.

Benefits of technology

By regulating the thin film crystallization process, the decomposition of formamidinium iodine is suppressed, grain growth is promoted, pinholes and grain boundary defects are reduced, and the device performance of perovskite photovoltaic cells is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120957578A_ABST
    Figure CN120957578A_ABST
Patent Text Reader

Abstract

The invention discloses a perovskite precursor solution additive, a perovskite light absorption layer and a preparation method of the perovskite light absorption layer. The preparation method of the perovskite solar cell comprises the following steps: adding a mixed solution of deionized water containing hydrochloric acid or organic amine hydrochloride and DMF (Dimethyl Formamide) into a perovskite solution to form a perovskite precursor solution, further obtaining a perovskite light absorption layer through a film preparation process, and assembling the solar cell. The crystallization process of the thin film is adjusted through chloride ions, hydroxyl and amino in the aqueous solution of hydrochloric acid or organic amine hydrochloride, decomposition of formamidine iodide is inhibited, growth of crystal grains is promoted, the quality of the thin film is improved, pinhole and grain boundary defects are reduced, and therefore the device performance of a perovskite photovoltaic cell prepared in air is enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of organic optoelectronic technology, and specifically relates to a perovskite precursor solution additive, a perovskite solar cell, and a preparation method thereof. Background Technology

[0002] Metal halide perovskites possess excellent photoelectric properties and hold immense potential for developing high-performance, cost-effective optoelectronic materials. Perovskite solar cells, as star devices in the future of photovoltaic development, have seen their photoelectric efficiency increase from 3.8% to 26.7% in just a few decades—a faster rate than silicon—and their photoelectric efficiency is gradually becoming comparable to that of silicon, the leader in photovoltaics. The sheer scale and speed of their development are astonishing. As perovskite technology matures, commercialization is an inevitable path for its development. The shared vision is to continue improving the efficiency, stability, and commercialization of perovskite solar cells, while simultaneously addressing the various inherent challenges of perovskite itself.

[0003] On the road to commercial applications, how to fabricate stable and reliable perovskite devices in air is a problem that must be solved. However, when fabricating perovskite devices in air, defects often easily arise at grain boundaries and interfaces. These defects lead to ion migration, and the perovskite material itself is sensitive to water and oxygen, so the stability of perovskite solar cells under actual operating conditions, such as heating, electric fields, and illumination, is still not satisfactory. Therefore, it is necessary to provide an improved method for fabricating perovskite light-absorbing layers to solve the above problems. Summary of the Invention

[0004] To address the above technical problems, the present invention aims to provide a perovskite precursor solution additive, a perovskite light-absorbing layer, and a method for preparing the same. The additive uses a mixed solution of DMF (hydrochloric acid or organic amine hydrochloride) and deionized water to regulate perovskite crystallization. Annealing in air alters the perovskite film grain size, reduces defects, and achieves better device performance.

[0005] To achieve the above objectives, the present invention provides a method for preparing a perovskite light-absorbing layer, comprising: adding a mixed solution of hydrochloric acid or organic amine hydrochloride DMF and deionized water to a perovskite solution to obtain a perovskite precursor solution, and then forming a film to obtain a perovskite light-absorbing layer.

[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows:

[0007] I. An additive for a perovskite precursor solution:

[0008] The additive is a mixed solution containing hydrochloric acid and / or organic amine hydrochloride, wherein the solvent of the mixed solution contains dimethylformamide (DMF) and deionized water;

[0009] The mixing volume ratio of DMF and deionized water is (18-25):1, preferably (22-25):1;

[0010] The concentration of the hydrochloric acid and / or organic amine hydrochloride in the solution is 1–30 mg / mL.

[0011] II. A method for preparing a perovskite light-absorbing layer, comprising:

[0012] The additives, a mixture of dimethylformamide (DMF) containing hydrochloric acid and / or organic amine hydrochloride and deionized water, are added to the original perovskite solution to obtain a perovskite precursor solution, and then a perovskite light-absorbing layer is formed using the perovskite precursor solution.

[0013] The DMF refers to dimethylacetamide.

[0014] The hydrochloric acid and / or organic amine hydrochloride is one or a mixture of hydrochloric acid, 3-chloropropylamine hydrochloride and isobutylamine hydrochloride;

[0015] The solvent for the additive comprises DMF and deionized water, with a mixing volume ratio of (18-25):1, preferably (22-25):1.

[0016] When the hydrochloric acid or organic amine hydrochloride is hydrochloric acid, 1 to 30 μL of hydrochloric acid is added to each 1 mL of the mixed solution, and the concentration of hydrochloric acid is 36 to 38%.

[0017] When the hydrochloric acid or organic amine hydrochloride is 3-chloropropylamine hydrochloride, 1 to 30 mg of 3-chloropropylamine hydrochloride is added to each 1 mL of the perovskite solution;

[0018] When the hydrochloric acid or organic amine hydrochloride is 3-chloropropylamine hydrochloride, 1 to 30 mg of isobutylamine hydrochloride is added to each 1 mL of the perovskite solution.

[0019] When the hydrochloric acid or organic amine hydrochloride is hydrochloric acid, 100-300 μL of a mixed solution containing hydrochloric acid is added to every 1 mL of the perovskite solution, and the hydrochloric acid concentration is 36-38%.

[0020] When the hydrochloric acid or organic amine hydrochloride is 3-chloropropylamine hydrochloride, 100-300 μL of a mixed solution containing 3-chloropropylamine hydrochloride is added to every 1 mL of the perovskite solution, and the concentration of 3-chloropropylamine hydrochloride is 1-30 mg / mL.

[0021] When the hydrochloric acid or organic amine hydrochloride is isobutylamine hydrochloride, 100-300 μL of a mixed solution containing isobutylamine hydrochloride is added to every 1 mL of the perovskite solution, and the concentration of isobutylamine hydrochloride is 1-30 mg / mL.

[0022] The solvent of the original perovskite solution comprises a mixture of DMF and NMP or a mixture of DMF and DMSO, wherein the volume ratio of DMF to NMP is (5-8):1 and the volume ratio of DMF to DMSO is (3-6):1.

[0023] The perovskite raw material in the original perovskite solution includes halides of element A and element B, and the resulting perovskite layer material has the structural formula ABX3; wherein, A is one or more of the cations Cs, MA, and FA, for example, the cation at the A site of the perovskite can be Cs. 0.05 MA 0.1 FA 0.85 The composition of the compound; B is one or more of Pb and Sn; X is one or more of Cl, Br, and I.

[0024] A is Cs, MA, FA; B is Pb; X is Br, I.

[0025] Preferably, the structural formula of the formal perovskite layer material is FAPbI3; preferably, the structural formula of the inverse perovskite layer material is Cs. a MA b FA c Pb(I d Br e )3; Perovskite layer composition in FAPbI3 and Cs a MA b FA c Pb(I d Br e Choose one of the following three options: a+b+c=1, a:b=1:(0~1), (a+b):c=(0.5~1):9.

[0026] The preparation method specifically involves dissolving perovskite raw material in a solution to form a raw perovskite solution, then adding additives to the salt solution, mixing evenly, and then coating or spin-coating in an air atmosphere, followed by annealing to obtain a perovskite light-absorbing layer.

[0027] III. A type of perovskite solar cell:

[0028] A formal perovskite solar cell includes an ITO transparent conductive substrate, and an electron transport layer, a perovskite light-absorbing layer, a hole transport layer, an electron blocking layer, and a metal electrode sequentially stacked on the transparent conductive substrate.

[0029] The inverted perovskite solar cell includes an FTO transparent conductive substrate, and a hole transport layer, a perovskite light-absorbing layer, an electron transport layer, a hole blocking layer, and a metal electrode sequentially stacked on the transparent conductive substrate.

[0030] The perovskite light-absorbing layer is prepared using the aforementioned method.

[0031] IV. A method for fabricating a nip-structured perovskite solar cell, comprising:

[0032] An electron transport layer is assembled on the surface of a conductive glass;

[0033] A perovskite precursor solution containing additives is coated onto the electron transport layer and heated to generate a perovskite light-absorbing layer; the additives are the perovskite precursor solution additives mentioned above.

[0034] A hole transport layer and a back electrode are assembled on the surface of the perovskite light-absorbing layer.

[0035] Preferably, the step of coating the perovskite precursor solution containing additives onto the electron transport layer and heating it to generate a perovskite light-absorbing layer includes:

[0036] Prepare perovskite precursor solutions with a concentration of 1–2 mol / L;

[0037] The additive at a concentration of 100-300 μL / mL was added to the perovskite precursor solution.

[0038] A perovskite precursor solution containing the additive is coated onto the electron transport layer and annealed at 100–150°C for 10–30 minutes.

[0039] V. A method for fabricating a pin-structured perovskite solar cell, comprising:

[0040] Assemble a hole transport layer or SAM layer on the surface of conductive glass;

[0041] A perovskite precursor solution containing additives is coated onto the hole transport layer or SAM layer and heated to generate a perovskite light-absorbing layer; the additives are the perovskite precursor solution additives.

[0042] An electron transport layer and a back electrode are assembled on the surface of the perovskite light-absorbing layer.

[0043] Preferably, the step of coating the perovskite precursor solution containing additives onto the hole transport layer or SAM layer and heating it to generate a perovskite light-absorbing layer includes:

[0044] Prepare perovskite precursor solutions with a concentration of 1–2 mol / L;

[0045] The additive at a concentration of 100-300 μL / mL was added to the perovskite precursor solution.

[0046] A perovskite precursor solution containing the additive is coated onto the hole transport layer or SAM layer and annealed at 100–120°C for 10–30 minutes.

[0047] Preferably, the hole transport layer is one of nickel oxide, cuprous oxide, cuprous sulfide, cuprous thiocyanate, cuprous iodide, 3-hexylthiophene, and 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirodifluorene;

[0048] The SAM layer comprises one of [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid, [2-(3,6-dimethyl-9H-carbazole-9-yl)ethyl]phosphonic acid, [4-(3,6-dimethoxy-9H-carbazole-9-yl)butyl]phosphonic acid, [4-(9H-carbazole-9-yl)butyl]phosphonic acid, [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid, and [2-(9H-carbazole-9-yl)ethyl]phosphonic acid.

[0049] Preferably, the electron transport layer is one of [6,6]-phenyl C61 butyrate methyl ester, [6,6]-phenyl C71 butyrate methyl ester, fullerene, SnO2, TiO2, and ZnO.

[0050] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0051] This invention regulates the crystallization process of the thin film by using chloride ions, hydroxyl groups, and amino groups in an aqueous solution of hydrochloric acid and organic amine hydrochloride, and inhibits the decomposition of formamidinium iodide, thereby promoting grain growth, improving film quality, reducing pinholes and grain boundary defects, and thus enhancing the device performance of perovskite photovoltaic cells prepared in air. Attached Figure Description

[0052] Figure 1 This is a structural diagram of a perovskite solar cell with a pin structure prepared according to an embodiment of the present invention;

[0053] Figure 2 This is a structural diagram of the nip structure perovskite solar cell prepared according to an embodiment of the present invention;

[0054] Figure 3 The diagram shows the current-voltage curves of the perovskite solar cells prepared in Example 1 and Comparative Example 1 of this invention.

[0055] Figure 4The figures show the current-voltage curves of the perovskite solar cells prepared in Example 2 and Comparative Example 2 of this invention.

[0056] Figure 5 The image shows the current-voltage curves of the perovskite solar cells prepared in Example 3 and Comparative Example 3 of this invention.

[0057] Figure 6 The current-voltage curves are shown for the perovskite solar cells prepared in Example 4 and Comparative Example 4 of this invention. Detailed Implementation

[0058] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0059] It should be noted that, unless otherwise specified, the features in the following embodiments and implementation methods can be combined with each other.

[0060] Unless otherwise specified in the embodiments of this invention, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be obtained through conventional technical means or commercially available.

[0061] In a first aspect, the present invention provides a perovskite precursor solution additive, which is added to a perovskite precursor solution.

[0062] The additives in this invention are hydrochloric acid with a concentration of 1-3 μL / mL or organic amine hydrochloride with a concentration of 1-3 mg / mL.

[0063] The perovskite precursor solutions in this invention include, but are not limited to, methylamine lead iodine (MAPbI3), methylamine lead bromide (MAPbBr3), formamidinium lead iodine (FAPbI3), formamidinium lead bromide (FAPbBr3), cesium lead iodine (CsPbI3), cesium lead bromide (CsPbBr3), methylamine tin iodine (MASnI3), methylamine tin bromide (MASnBr3), and mixtures thereof.

[0064] Furthermore, the organic amine hydrochloride may be one or more of 3-chloropropylamine hydrochloride and isobutylamine hydrochloride.

[0065] In a second aspect, the present invention provides a perovskite solar cell, comprising a conductive glass substrate, a carrier transport layer, a perovskite light-absorbing layer and a back electrode, wherein the perovskite light-absorbing layer comprises the aforementioned perovskite precursor solution additive.

[0066] Thirdly, the present invention provides a method for fabricating a nip-structured perovskite solar cell, the fabrication process being as follows:

[0067] Step 1: The conductive glass substrate is ultrasonically cleaned in deionized water, acetone and ethanol solutions in sequence, dried with nitrogen, and then treated in an ultraviolet ozone cleaner for 10 to 30 minutes. An electron transport layer is assembled on the surface of the substrate by coating or vapor deposition.

[0068] In this step, the electron transport layer is generally a metal oxide such as SnO2, TiO2, or ZnO.

[0069] Step 2: Prepare a perovskite precursor solution with a concentration of 1-2 mol / L, and add a mixed solution containing hydrochloric acid or organic amine hydrochloride at a concentration of 10-30 μL / mL. Coat the perovskite precursor solution containing hydrochloric acid or organic amine hydrochloride onto the electron transport layer substrate and anneal at 100-150°C for 10-30 minutes to generate a perovskite light-absorbing layer.

[0070] In this step, the perovskite precursor solution includes, but is not limited to, methylamine lead iodine (MAPbI3), methylamine lead bromide (MAPbBr3), formamidinium lead iodine (FAPbI3), formamidinium lead bromide (FAPbBr3), cesium lead iodine (CsPbI3), cesium lead bromide (CsPbBr3), methylamine tin iodine (MASnI3), methylamine tin bromide (MASnBr3), and mixtures thereof.

[0071] In this step, the hydrochloric acid component can be replaced by one or more of the organic amine hydrochloride components, such as 3-chloropropylamine hydrochloride and isobutylamine hydrochloride.

[0072] Step 3: Assemble the hole transport layer on the perovskite light-absorbing substrate and deposit the back electrode.

[0073] In this step, the hole transport layer includes metal oxide materials such as nickel oxide, copper oxide, copper sulfide, and cuprous sulfide, as well as organic materials such as 3-hexylthiophene (P3HT) and 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirodifluorene (Spiro-OMeTAD).

[0074] Fourthly, the present invention provides a method for fabricating a pin-structured perovskite solar cell, the fabrication process of which is as follows:

[0075] Step 1: The conductive glass substrate is ultrasonically cleaned in deionized water, acetone and ethanol solutions in sequence, dried with nitrogen, and then treated in an ultraviolet ozone cleaner for 10 to 30 minutes. Hole transport layer or SAM layer is assembled on the substrate surface by coating or vapor deposition.

[0076] In this step, the hole transport layer includes inorganic materials such as nickel oxide, cuprous oxide, cuprous sulfide, cuprous thiocyanate, and cuprous iodide, as well as organic materials such as 3-hexylthiophene (P3HT) and 2,2',7,7'-tetra[N,N-di(4-methoxyphenyl)amino]-9,9'-spirodifluorene (Spiro-OMeTAD).

[0077] In this step, the SAM layer includes [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid (Me-4PACz), [2-(3,6-dimethyl-9H-carbazole-9-yl)ethyl]phosphonic acid (Me-2PACz), [4-(3,6-dimethoxy-9H-carbazole-9-yl)butyl]phosphonic acid (MeO-4PACz), [4-(9H-carbazole-9-yl)butyl]phosphonic acid (4PACz), [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid (MeO-2PACz), and [2-(9H-carbazole-9-yl)ethyl]phosphonic acid (2PACz), etc.

[0078] Step 2: Prepare a perovskite precursor solution with a concentration of 1-2 mol / L, and add a mixed solution containing hydrochloric acid or organic amine hydrochloride at a concentration of 10-30 μL / mL to the solution. Coat the perovskite precursor solution with added hydrochloric acid or organic amine hydrochloride onto the hole transport layer substrate and anneal at 100-120°C for 10-30 minutes.

[0079] In this step, the perovskite precursor solution includes, but is not limited to, methylamine lead iodine (MAPbI3), methylamine lead bromide (MAPbBr3), formamidinium lead iodine (FAPbI3), formamidinium lead bromide (FAPbBr3), cesium lead iodine (CsPbI3), cesium lead bromide (CsPbBr3), methylamine tin iodine (MASnI3), methylamine tin bromide (MASnBr3), and mixtures thereof.

[0080] In this step, the hydrochloric acid component can be replaced by one or more of the organic amine hydrochloride components, such as 3-chloropropylamine hydrochloride and isobutylamine hydrochloride.

[0081] Step 3: Assemble the electron transport layer on the hole transport layer substrate and deposit the back electrode.

[0082] In this step, the electron transport layer includes methyl [6,6]-phenyl C61 butyrate (PC). 61 BM), [6,6]-phenyl C71 butyrate methyl ester (PC) 71 BM), fullerene (C) 60 Organic compounds such as SnO2, TiO2, ZnO and other metal oxides.

[0083] The above-described perovskite solar cells with nip and pin structures were prepared, their performance was tested, and compared with that of perovskite solar cells without additives.

[0084] Example 1

[0085] The ITO conductive glass substrate was ultrasonically cleaned sequentially in deionized water, acetone and ethanol solutions, dried with nitrogen, and then treated in an ultraviolet ozone cleaner for 30 minutes. The SnO2 nanocolloid solution was spin-coated onto the ITO glass surface and then annealed on a hot stage at 150°C for 0.5 hours to obtain the SnO2 electron transport layer.

[0086] Equimolar amounts of FAI and PbI₂ were dissolved in a mixed solvent of DMF and NMP at a solvent ratio of 6:1 to form a perovskite precursor solution with a concentration of 1.6 mol / L. A mixed solvent of DMF containing hydrochloric acid and deionized water at a solvent ratio of 24:1 and a concentration of 150 μL / mL was added to the perovskite precursor solution. The solution was deposited onto an ITO / ETL substrate at a rotation speed of 4000 rpm for 12 seconds. All the obtained perovskite precursor wet films were then transferred to a vacuum chamber and pumped at approximately 20 Pa for 45 seconds. The ITO glass was then heated on a hot stage at 150 °C for 30 minutes to obtain the perovskite light-absorbing layer.

[0087] An acetonitrile solution containing 4-tert-butylpyridine (tBP) and Li-TFSI was mixed with a chlorobenzene solution of Spiro-OMeTAD and spin-coated onto a perovskite light-absorbing substrate as a hole transport layer.

[0088] Finally, the substrate was placed in an evaporator to deposit an 80nm silver film as the back electrode, thus fabricating a nip-structured perovskite solar cell, such as... Figure 1 As shown.

[0089] Example 2

[0090] The FTO conductive glass was ultrasonically cleaned sequentially in deionized water, acetone, and ethanol solutions, dried with nitrogen, and then treated in a UV ozone cleaner for 20 minutes. The glass containing NiO... X An aqueous solution was spin-coated onto the FTO glass surface and then annealed at 150°C for 10 min to obtain a nickel oxide layer. An ethanol solution containing 2 PACz was spin-coated onto the nickel oxide layer surface and then annealed at 100°C for 15 min to obtain a SAM layer.

[0091] FAPbI3, MAPbBr3, and CsPbI3 were dissolved in a mixed solvent of DMF and NMP (DMF to NMP molar ratio 9:1) at a molar ratio of 18:1:1 to form a perovskite precursor solution with a total molar amount of 1.6 mol / L. A mixed solvent of DMF containing hydrochloric acid and deionized water was added to the perovskite precursor solution at a solvent ratio of 24:1 and a concentration of 150 μL / mL. The solution was deposited on an FTO / HTL substrate at a rotation speed of 4000 rpm for 15 seconds. All the obtained perovskite precursor wet films were then transferred to a vacuum chamber and pumped at approximately 20 Pa for 45 seconds. The samples were then heated on a hot stage at 100 °C for 20 minutes to obtain the perovskite light-absorbing layer.

[0092] Will contain PC 61 BM’s chlorobenzene solution and copper bath isopropanol solution were spin-coated onto the perovskite light-absorbing substrate as electron transport layer and hole blocking layer, respectively.

[0093] Finally, the substrate was placed in a magnetron sputtering apparatus, and a 100 nm silver film was vacuum sputtered as the back electrode. This yielded a pin-structured perovskite solar cell, such as... Figure 2 As shown.

[0094] Example 3

[0095] The FTO conductive glass was ultrasonically cleaned sequentially in deionized water, acetone, and ethanol solutions, dried with nitrogen, and then treated in a UV ozone cleaner for 20 minutes. The glass containing NiO... X An aqueous solution of Me-4PACz was spin-coated onto the surface of FTO glass and then annealed at 150°C for 10 min to obtain a nickel oxide layer. An ethanol solution containing Me-4PACz was spin-coated onto the surface of the nickel oxide layer and then annealed at 100°C for 15 min to obtain a SAM layer.

[0096] FAPbI3, MAPbBr3, and CsPbI3 were dissolved in a mixed solvent of DMF and NMP (DMF to NMP molar ratio 9:1) at a molar ratio of 18:1:1 to form a perovskite precursor solution with a total molar amount of 1.6 mol / L. A mixed solvent of DMF containing isobutylamine hydrochloride and deionized water was added to the perovskite precursor solution at a solvent ratio of 24:1 and a concentration of 150 μL / mL. The mixture was deposited on an FTO / HTL substrate at 4000 rpm for 15 seconds. All the obtained perovskite precursor wet films were then transferred to a vacuum chamber and pumped at approximately 20 Pa for 45 seconds. The samples were then heated on a hot stage at 100 °C for 20 minutes to obtain the perovskite light-absorbing layer.

[0097] Will contain PC 61BM’s chlorobenzene solution (20 mg / mL) and copper bath isopropanol solution (0.5 mg / mL) were spin-coated onto the perovskite light-absorbing substrate as electron transport layer and hole blocking layer, respectively.

[0098] Finally, the substrate was placed in a magnetron sputtering apparatus, and a 100 nm silver film was vacuum sputtered as the back electrode. This yielded a pin-structured perovskite solar cell, such as... Figure 2 As shown.

[0099] Example 4

[0100] The FTO conductive glass was ultrasonically cleaned sequentially in deionized water, acetone, and ethanol solutions, dried with nitrogen, and then treated in a UV ozone cleaner for 20 minutes. An ethanol solution containing 2 PACz was spin-coated onto the FTO glass surface, and then annealed at 100°C for 15 minutes to obtain the SAM layer.

[0101] FAPbI3 and CsPbI3 were dissolved in a mixed solvent of DMF and DMSO (DMF to DMSO molar ratio 4:1) at a molar ratio of 12:1 to form a perovskite precursor solution with a total molar amount of 1.4 mol / L. A mixed solvent of DMF containing 3-chloropropylamine hydrochloride and deionized water was added to the perovskite precursor solution at a solvent ratio of 24:1 and a concentration of 150 μL / mL. The solution was deposited on an FTO / HTL substrate at a rotation speed of 4000 rpm for 25 seconds. All the obtained perovskite precursor wet films were then transferred to a vacuum chamber and pumped at approximately 20 Pa for 45 seconds. An ITO glass was then heated on a hot stage at 120 °C for 20 minutes to obtain the perovskite light-absorbing layer.

[0102] Will contain PC 61 BM’s chlorobenzene solution (20 mg / mL) and copper bath isopropanol solution (0.5 mg / mL) were spin-coated onto the perovskite light-absorbing substrate as electron transport layer and hole blocking layer, respectively.

[0103] Finally, the substrate was placed in a magnetron sputtering instrument, and an 80 nm silver film was vacuum sputtered as the back electrode to prepare a pin-structured perovskite solar cell.

[0104] Comparative Example 1 (without high-efficiency additives)

[0105] Comparative Example 1 is a comparative example of Example 1 above, except that no additives were prepared in the perovskite light-absorbing layer of Comparative Example 1. The rest of the preparation process is the same as that of Example 1 above, and the preparation process is as follows:

[0106] The ITO conductive glass was ultrasonically cleaned sequentially in deionized water, acetone and ethanol solutions, dried with nitrogen, and then treated in an ultraviolet ozone cleaner for 10 minutes. The SnO2 nanocolloid solution was spin-coated onto the surface of the ITO glass and then annealed on a hot stage at 150°C for 0.5 hours to obtain the SnO2 electron transport layer.

[0107] Equimolar amounts of FAI and PbI₂ were dissolved in a mixed solvent of DMF and NMP at a solvent ratio of 6:1 to form a perovskite precursor solution with a concentration of 1.4 mol / L. This solution was deposited on an ITO / ETL substrate at a rotation speed of 4000 rpm for 12 seconds. All the obtained perovskite precursor wet films were then transferred to a vacuum chamber and pumped at approximately 20 Pa for 45 seconds. The ITO glass was then heated on a hot stage at 150 °C for 30 minutes to obtain the perovskite light-absorbing layer.

[0108] An acetonitrile solution containing 4-tert-butylpyridine (tBP) and Li-TFSI was mixed with a chlorobenzene solution of Spiro-OMeTAD and spin-coated onto a perovskite substrate as a hole transport layer.

[0109] Finally, the substrate was placed in an evaporation apparatus to deposit an 80nm silver film as the back electrode, thus preparing a perovskite solar cell with a nip structure.

[0110] Comparative Example 2 (without high-efficiency additives)

[0111] Comparative Example 2 is a comparative example of Example 2 above, except that no additives were prepared in the perovskite light-absorbing layer of Comparative Example 2. The rest of the preparation process is the same as that of Example 2 above, and the preparation process is as follows:

[0112] The FTO conductive glass was ultrasonically cleaned sequentially in deionized water, acetone, and ethanol solutions, dried with nitrogen, and then treated in a UV ozone cleaner for 20 minutes. The glass containing NiO... X An aqueous solution was spin-coated onto the FTO glass surface and then annealed at 150°C for 10 min to obtain a nickel oxide layer. An ethanol solution containing 2 PACz was spin-coated onto the nickel oxide layer surface and then annealed at 100°C for 15 min to obtain a SAM layer.

[0113] FAPbI3, MAPbBr3, and CsPbI3 were dissolved in a mixed solvent of DMF and NMP (DMF to NMP molar ratio 9:1) at a molar ratio of 18:1:1 to form a perovskite precursor solution with a total molar amount of 1.6 mol / L. This solution was deposited on an FTO / HTL substrate at 4000 rpm for 25 seconds. All the obtained perovskite precursor wet films were then transferred to a vacuum chamber and pumped at approximately 20 Pa for 45 seconds. The samples were then heated on a 100°C hot stage for 20 minutes to obtain the perovskite light-absorbing layer.

[0114] Will contain PC 61 BM’s chlorobenzene solution (20 mg / mL) and copper bath isopropanol solution (0.5 mg / mL) were spin-coated onto the perovskite light-absorbing substrate as electron transport layer and hole blocking layer, respectively.

[0115] Finally, the substrate was placed in a magnetron sputtering apparatus, and a 100 nm silver film was vacuum sputtered as the back electrode. This yielded a pin-structured perovskite solar cell, such as... Figure 2 As shown.

[0116] Comparative Example 3 (without high-efficiency additives)

[0117] Comparative Example 3 is a comparative example of Example 3 above, except that no additives were prepared in the perovskite light-absorbing layer of Comparative Example 3. The rest of the preparation process is the same as that of Example 1 above, and the preparation process is as follows:

[0118] The FTO conductive glass was ultrasonically cleaned sequentially in deionized water, acetone, and ethanol solutions, dried with nitrogen, and then treated in a UV ozone cleaner for 20 minutes. The glass containing NiO... X An aqueous solution was spin-coated onto the FTO glass surface and then annealed at 150°C for 10 min to obtain a nickel oxide layer. An ethanol solution containing 2 PACz was spin-coated onto the nickel oxide layer surface and then annealed at 100°C for 15 min to obtain a SAM layer.

[0119] FAPbI3, MAPbBr3, and CsPbI3 were dissolved in a mixed solvent of DMF and NMP (DMF to NMP molar ratio 9:1) at a molar ratio of 18:1:1 to form a perovskite precursor solution with a total molar amount of 1.6 mol / L. This solution was deposited on an FTO / HTL substrate at 4000 rpm for 15 seconds. All the obtained perovskite precursor wet films were then transferred to a vacuum chamber and pumped at approximately 20 Pa for 45 seconds. The samples were then heated on a 100°C hot stage for 20 minutes to obtain the perovskite light-absorbing layer.

[0120] Will contain PC 61 BM’s chlorobenzene solution (20 mg / mL) and copper bath isopropanol solution (0.5 mg / mL) were spin-coated onto the perovskite light-absorbing substrate as electron transport layer and hole blocking layer, respectively.

[0121] Finally, the substrate was placed in a magnetron sputtering apparatus, and a 100 nm silver film was vacuum sputtered as the back electrode. This yielded a pin-structured perovskite solar cell, such as... Figure 2 As shown.

[0122] Comparative Example 4 (without high-efficiency additives)

[0123] The FTO conductive glass was ultrasonically cleaned sequentially in deionized water, acetone, and ethanol solutions, dried with nitrogen, and then treated in a UV ozone cleaner for 20 minutes. An ethanol solution containing 2 PACz was spin-coated onto the FTO glass surface, and then annealed at 100°C for 15 minutes to obtain the SAM layer.

[0124] FAPbI3 and CsPbI3 were dissolved in a mixed solvent of DMF and DMSO (molar ratio of DMF to DMSO: 1:4) at a molar ratio of 12:1 to form a perovskite precursor solution with a total molar amount of 1.4 mol / L. This solution was deposited on an FTO / HTL substrate at 4000 rpm for 25 seconds. All the obtained perovskite precursor wet films were then transferred to a vacuum chamber and pumped at approximately 20 Pa for 45 seconds. The samples were then heated on a hot stage at 120 °C for 20 minutes to obtain the perovskite light-absorbing layer.

[0125] Will contain PC 61 BM’s chlorobenzene solution (20 mg / mL) and copper bath isopropanol solution (0.5 mg / mL) were spin-coated onto the perovskite light-absorbing substrate as electron transport layer and hole blocking layer, respectively.

[0126] Finally, the substrate was placed in a magnetron sputtering instrument, and an 80 nm silver film was vacuum sputtered as the back electrode to prepare a pin-structured perovskite solar cell.

[0127] The perovskite solar cells prepared in Examples 1-4 and Comparative Examples 1-4 were tested to obtain the IV test curves of each prepared perovskite solar cell, and the photoelectric conversion efficiency was calculated. Figures 3-6 It is evident that the batteries prepared in Examples 1-4 have significantly higher efficiencies than those in the comparative examples. Therefore, the use of the high-efficiency additives described in this invention to prepare perovskite batteries can improve the photoelectric conversion efficiency of the batteries.

[0128] Other embodiments of this application will readily occur to those skilled in the art upon consideration of the specification and practice of the disclosure herein. This application is intended to cover any variations, uses, or adaptations of this application that follow the general principles of this application and include common knowledge or customary techniques in the art not disclosed herein.

[0129] It should be understood that this application is not limited to the precise structure described above and shown in the accompanying drawings, and various modifications and changes can be made without departing from its scope.

Claims

1. An additive for a perovskite precursor solution, characterized in that, The additive is a mixed solution containing hydrochloric acid and / or organic amine hydrochloride, wherein the solvent of the mixed solution contains dimethylformamide (DMF) and deionized water; The mixing volume ratio of DMF and deionized water is (18-25):1; The concentration of the hydrochloric acid and / or organic amine hydrochloride in the solution is 1–30 mg / mL.

2. A method for preparing a perovskite light-absorbing layer based on the additive described in claim 1, characterized in that, include: The additives, a mixture of dimethylformamide (DMF) containing hydrochloric acid and / or organic amine hydrochloride and deionized water, are added to the original perovskite solution to obtain a perovskite precursor solution, and then a perovskite light-absorbing layer is formed using the perovskite precursor solution.

3. The method for preparing a perovskite light-absorbing layer according to claim 2, characterized in that, The hydrochloric acid and / or organic amine hydrochloride is one or a mixture of hydrochloric acid, 3-chloropropylamine hydrochloride and isobutylamine hydrochloride; The volume ratio of the additive's DMF to deionized water is (18-25):

1.

4. The method for preparing a perovskite light-absorbing layer according to claim 3, characterized in that, When the hydrochloric acid or organic amine hydrochloride is hydrochloric acid, 1 to 30 μL of hydrochloric acid is added to each 1 mL of the mixed solution, and the concentration of hydrochloric acid is 36 to 38%. When the hydrochloric acid or organic amine hydrochloride is 3-chloropropylamine hydrochloride, 1 to 30 mg of 3-chloropropylamine hydrochloride is added to each 1 mL of the perovskite solution; When the hydrochloric acid or organic amine hydrochloride is 3-chloropropylamine hydrochloride, 1 to 30 mg of isobutylamine hydrochloride is added to each 1 mL of the perovskite solution.

5. The method for preparing a perovskite light-absorbing layer according to claim 3, characterized in that, When the hydrochloric acid or organic amine hydrochloride is hydrochloric acid, 100-300 μL of a mixed solution containing hydrochloric acid is added to every 1 mL of the perovskite solution, and the hydrochloric acid concentration is 36-38%. When the hydrochloric acid or organic amine hydrochloride is 3-chloropropylamine hydrochloride, 100-300 μL of a mixed solution containing 3-chloropropylamine hydrochloride is added to every 1 mL of the perovskite solution, and the concentration of 3-chloropropylamine hydrochloride is 1-30 mg / mL. When the hydrochloric acid or organic amine hydrochloride is isobutylamine hydrochloride, 100-300 μL of a mixed solution containing isobutylamine hydrochloride is added to every 1 mL of the perovskite solution, and the concentration of isobutylamine hydrochloride is 1-30 mg / mL.

6. A method for preparing a perovskite light-absorbing layer according to any one of claims 2-5, characterized in that, The solvent of the original perovskite solution comprises a mixture of DMF and NMP or a mixture of DMF and DMSO, wherein the volume ratio of DMF to NMP is (5-8):1 and the volume ratio of DMF to DMSO is (3-6):

1.

7. A method for preparing a perovskite light-absorbing layer according to any one of claims 2-5, characterized in that, The perovskite raw material in the original perovskite solution includes halides of element A and halides of element B, and the structural formula of the resulting perovskite layer material is ABX3; wherein, A is one or more of the cations Cs, MA, and FA; B is one or more of Pb and Sn; and X is one or more of Cl, Br, and I.

8. The method for preparing a perovskite light-absorbing layer according to claim 7, characterized in that... A is Cs, MA, FA; B is Pb; X is Br, I.

9. A method for preparing a perovskite light-absorbing layer according to any one of claims 7-8, characterized in that, The preparation method specifically involves dissolving perovskite raw material in a solution to form a raw perovskite solution, then adding the additive, mixing evenly, and then coating or spin-coating in an air atmosphere, followed by annealing to obtain a perovskite light-absorbing layer.

10. A perovskite solar cell, characterized in that, A formal perovskite solar cell includes an ITO transparent conductive substrate, and an electron transport layer, a perovskite light-absorbing layer, a hole transport layer, an electron blocking layer, and a metal electrode sequentially stacked on the transparent conductive substrate. The inverted perovskite solar cell includes an FTO transparent conductive substrate, and a hole transport layer, a perovskite light-absorbing layer, an electron transport layer, a hole blocking layer, and a metal electrode sequentially stacked on the transparent conductive substrate. The perovskite light-absorbing layer is prepared by the preparation method described in any one of claims 2-9.

Citation Information

Cited By

  • Large-area hybrid perovskite photovoltaic cell and preparation method thereof

    CN121772478A

  • Large-area hybrid perovskite photovoltaic cells and methods of making the same

    CN121772478B